2014
DOI: 10.11648/j.js.20140203.11
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Liver Enzymes in Patients with Cholecystitis

Abstract: Aims: To investigate changes in liver function tests in calcular cholecystitis (acute and chronic) and to relate that changes to cholecystitis. Methods: A retrospective study including 389 patients with clinical and sonographic evidence of cholecystitis with exclusion of other causes of elevated liver function tests, which are done preoperatively and four weeks postoperatively. Results: Increased liver function tests observed in both acute and chronic cholecystitis. The only significant differences between bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…As previously observed in the literature,81324 LFTs including total bilirubin, SGOT and ALP can vary in AC patients with or without CBDS. They are not only affected by the presence of CBDS but also by the severity and acuteness of AC 25. Our study showed that both AC + and AC − patients could present with normal results.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As previously observed in the literature,81324 LFTs including total bilirubin, SGOT and ALP can vary in AC patients with or without CBDS. They are not only affected by the presence of CBDS but also by the severity and acuteness of AC 25. Our study showed that both AC + and AC − patients could present with normal results.…”
Section: Discussionmentioning
confidence: 53%
“…There are several mechanisms may be responsible for the false negative and false positive LFTs in AC patients. In theory, CBD stones cause biliary obstruction with increased intra-biliary pressure due to hindrance of bile flow and subsequent peri-ductal inflammation and hepatocellular injury with elevated LFTs 81025. However, partially obstructing stones may not cause elevated bilirubin levels thus generating false negative values 713.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, on one hand, among patients without CBDS, CC cases have been reported to have significantly lower LFTs when compared to AC cases [13] . On the other hand, a study by Peng WK, Sheikh Z, Paterson-Brown S et al, on patients without CBDS showed no significant differences in LFTs between AC and CC patients [14] .…”
Section: Introductionmentioning
confidence: 95%
“…The changes in post-operative liver function tests (LFTs) after LC may also result from the potential hepatotoxicity of anesthetic drugs used during the procedure, and the thermal energy used for haemostatic control during gallbladder removal [6]. For instance, potential hepatocellular damage is identified with the elevation of serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) [7,8]. Increased level of alkaline phosphatase (ALP) is a result of biliary duct obstruction while haemolysis or bile flow obstruction increases bilirubin level.…”
Section: Introductionmentioning
confidence: 99%